PET-based copolyesters with bisphenol A or bisphenol F structural units: Their distinct differences in pyrolysis behaviours and flame-retardant performances. (October 2015) - Guo, De-Ming; Chen, Xiang-Quan; Tang, Liang; Wu, Jia-Ning; Fu, Teng; Wang, Xiao-Lin; Wang, Xiu-Li; Chen, Li; Wang, Yu-Zhong
Abstract: In order to avoid potential environmental and safety problems caused by conventional flame retardants, we synthesized the flame-retardant-element-free copolyesters via chemically incorporating the structural units of bisphenol A and bisphenol F into the PET main chain via melt polymerization, respectively. The chemical structures of resulting copolyesters were confirmed by 1 H NMR and 13 C NMR spectroscopy. Interestingly, though there exists only a small structural difference between bisphenol A and bisphenol F, those two kinds of copolyesters show different thermal stabilities, pyrolysis behaviours and flame retardant performances. Pyrolysis-GC/MS tests were performed to investigate the pyrolysis mechanism of the copolyesters, and the results showed that the "Ar–CH2 –Ar" structure units (bisphenol F) would lead to rearrangement reactions at high temperature, ultimately forming the phenanthrene ring structures; whereas "Ar–C(CH3 )2 −Ar" structure units (bisphenol A) could not. The corresponding specific pyrolysis processes are proposed. Thermogravimetric analysis (TGA) results indicated that these rearrangement reactions would most likely occur in the solid state of the copolyesters and made them have high residues. Cone calorimeter measurements, LOI and vertical UL-94 tests were used to characterize the flame-retardant properties of the copolyesters, and the results proved that the copolyesters containing bisphenol F had better flame retardancy, more char formation and less melt drippings than those containing bisphenol A due to the rearrangement reactions.